Decoupling between calorimetric and dynamical glass transitions in high-entropy metallic glasses - Jing Jiang (Nature Portfolio, 2021)
Here the authors study thermodynamic and dynamic glass transition of high entropy metallic glasses. Results show retarded α-relaxation and distinct crystallization resistance attributed to their sluggish diffusion and high-entropy mixing that is different from the traditional metallic glasses.